A Method of Circular Scleral Buckle Length Calculation in Retinal Detachment Surgery - V. N. Kazaykin; A. Yu. Kleymenov; E. M. Murashova; G. V. Chashchin (Oftalʹmologiâ, 2021)
Purpose. To develop a method of circular buckle length calculation for optimization of circular scleral buckling in retinal detachment surgery.Methods. At the first stage of the study a formula for calculation of optimal circular scleral buckle length for patients with various axial length (AL) of the eyeball was developed (90 eyes). These healthy eyes were divided into three groups, 30 eyes in each: group 1 — AL 19 to 23.5 mm, group 2 — AL 23.6 to 27 mm, group 3 — AL over 27 mm. In all the groups AL and equatorial diameter of the eyeball were measured with ultrasound A- and B- scanning (Тomey UD8000, Tomey AL 3000). Mathematic estimation of equatorial eyeball diameter dependence on AL was performed using correlation and regression analysis and the formula for optimal circular buckle length calculation was derived. At the second stage the derived formula was used in clinic during retinal detachment surgery in 15 eyes of 15 patients aged 28 to 44 years (37.6 ± 2.6) with subtotal retinal detachment occupying 2 to 3 quadrants. Follow-up period was 1 to 4 months (2.3 ± 0.5). For control, in all patient’s intraoperative measurement of the eyeball circumference in equatorial zone was performed.Results. The first step of the study revealed high correlation coefficient (r) between AL and equatorial eyeball diameter in groups 1 and 2, 0.89 and 0.87, respectively. In group 3 correlation coefficient was 0.57 which shows moderate correlation between AL and equatorial eyeball diameter. Group 3 (AL > 27 mm) was not included in deriving the formula for circular buckle length calculation. Finally, regression equation was obtained and the following formula for circular buckle length calculation was derived: L = 0.9π (8.05 + 0.66 AL), where L — circular buckle length, π = 3.14, AL — axial length of the eyeball. At the second stage of the study (eyes with AL less than 27 mm) anatomical attachment of the retina was achieved in all 15 cases (100 %), elevation of the buckle was 1.44 to 1.6 mm (1.5 ± 0.02), circular buckle shortening made 10 % of the initial eyeball diameter. Control measurement of eyeball diameter in equatorial zone coincided with calculated values, that is, equaled the data obtained from presented formula and from preoperative ultrasound measurement of equatorial eyeball diameter.Conclusions. The derived formula for circular buckle length calculation is highly effective for eyes with AL less than 27 mm: provides optimal height of impression roll (approximately 1.5 mm), reduces the risk of postoperative complications, it is simple in use and shortens the operation time. For calculation of circular buckle length for eyes with AL over 27 mm it is reasonable to use the data of preoperative ultrasound A-scan measurement of equatorial diameter of the eyeball.